Public administration quest for identity - Bhaskara Rao, V. 1939-.; Sharma, Arvind K.; Indian Institute of Public Administration (New Delhi Vikas Pub. House, 1996)
In Indian context; papers presented at a seminar held at Indian Institute of Public Administration, New Delhi, 1992.
Keywords: Public administration -- India; India -- Politics and government -- 1947-.